Estimation of Salivary IL-6 and Calprotectin in Patients with Ulcerative Colitis - Abdullah, Fadhel A.; A. Mahmood, Maha (Journal of the Faculty of Medicine Baghdad, 2024)
Background:  Inflammatory bowel disease is chronic inflammation of the gastrointestinal tract it includes two condition; Crohn’s disease and ulcerative colitis. Calprotectin released by keratinocytes, phagocytes, monocytes, granulocytes and vascular cells is recognized by toll-like receptors (TLRs) to induce inflammatory response.Objectives: In order to investigate if there are significant differences in the levels of those markers (IL6 and Calprotectin in between UC patients and healthy control subjects.Patients and Methods: The subjects included were twenty-five patients with ulcerative colitis and twenty-five healthy individuals as the control group. All of whom ranged in age from 20-55 years, and the levels of interleukin-6 (IL-6) and Calprotectin in the saliva of UC patients were measured using the ELISA methodResult: When compared to the control group, the current findings indicated that both (IL-6) and Calprotectin levels were significantly higher in UC patients, (P=